DISTANCE LEARNING PROBLEMS AND ITS SOLUTIONS - Denins, Andris (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The purpoise of this article is to provide a general guidance on designing and developing management of dietance learnin . It also deals with the different discloesed problems, solutions and methadological approaches for distance learning in high schools management study courses